2022
DOI: 10.3389/fmicb.2021.783284
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Distinct Characteristics of Antibiofilm Peptides and Prospection of Diverse Sources for Efficacious Sequences

Abstract: A majority of microbial infections are associated with biofilms. Targeting biofilms is considered an effective strategy to limit microbial virulence while minimizing the development of antibiotic resistance. Toward this need, antibiofilm peptides are an attractive arsenal since they are bestowed with properties orthogonal to small molecule drugs. In this work, we developed machine learning models to identify the distinguishing characteristics of known antibiofilm peptides, and to mine peptide databases from di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Thus, the most important or central peptides can be highlighted, and the edges weighted with high or low similarities. This work aimed at the outset to exploit the visual representation of complex networks representing ABFPs in order to analyze their structural space and associated metadata, both of which are relevant for the discovery and design of antibiofilm agents [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the most important or central peptides can be highlighted, and the edges weighted with high or low similarities. This work aimed at the outset to exploit the visual representation of complex networks representing ABFPs in order to analyze their structural space and associated metadata, both of which are relevant for the discovery and design of antibiofilm agents [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our motif search approach assisted by complex networks produced results that are not so far from the few findings reported in the literature. Recently, Anastasiu et al found that the following motifs “RIRV,” “RIVQRIK,” and “IGKEFKR” appeared with more frequency in 242 ABFPs collected from APD and BaAMP databases with respect to a curated negative set [ 31 ], when using the “MERCI” software [ 72 ]. In this sense, we agree with them in the detection of the “RIRV” which was fully integrated in the RIRVR motif detected in cluster 14 by the MAFFT algorithm, and also enriched in the BaAMP dataset.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DPC analysis revealed the high frequency of charged-hydrophobicity theme in antibiofilm peptides with significant antibiofilm effects. Bose et al indicated that these combinations of dipeptides outline the amphipathic characteristics of ABFs [58]. A comparison of DPC between hiABFs and QSPs is shows in Fig.…”
Section: Fig 8 Comparsion Of Physicochemical Properties Between Abfs ...mentioning
confidence: 95%